Development of a Novel Iron Remover for Potassium Chloride Zinc Plating Bath - SHEN Pin-hua, JIN Yu (Cailiao Baohu, 2021)
The bivalent iron in potassium chloride zinc plating solution reduced the current density range, resulting in black barrel eye marks on barrel plating products. Hydrogen peroxide could oxidize them to much less harmful trivalent iron, but it also reduced the dispersion of plating solution and oxidized some brightener. Besides, hydrogen peroxide was listed in the list of dangerous chemicals, which was difficult for purchase and storage. In order to solve the problem in the process of potassium chloride zinc plating, a kind of iron remover DF (mainly divalent iron chelating agent) for potassium chloride zinc plating solution without hydrogen peroxide was developed. Besides, its application performance was characterized by Hull cell test.